2007
DOI: 10.1091/mbc.e06-10-0968
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Translational Isoforms Give Functional Specificity to Serum- and Glucocorticoid-induced Kinase 1

Abstract: Serum-and glucocorticoid-induced kinase 1 is a ubiquitous kinase that regulates diverse processes such as ion transport and cell survival. We report that a single SGK1 mRNA produces isoforms with different N-termini owing to alternative translation initiation. The long isoforms, 49 and 47 kDa, are the most abundant, localize to the ER membrane, exhibit rapid turnover, their expression is decreased by ER stress, activate the epithelial sodium channel (ENaC) and translocate FoxO3a transcriptional factors from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…In a similar manner, removal of the N terminus of the canonical SGK1 eliminates regulation of ENaC (27). Therefore, this result confirms and extends our previous conclusion that correct subcellular localization is key for achieving functional specificity of the SGK1 isoforms (23). Regulation by compartmentation is partly overcome by rendering the cytosolic SGK1.1 mutants constitutively active because, owing to their distribution over the whole cell, they have access to substrates that cannot be reached under normal conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a similar manner, removal of the N terminus of the canonical SGK1 eliminates regulation of ENaC (27). Therefore, this result confirms and extends our previous conclusion that correct subcellular localization is key for achieving functional specificity of the SGK1 isoforms (23). Regulation by compartmentation is partly overcome by rendering the cytosolic SGK1.1 mutants constitutively active because, owing to their distribution over the whole cell, they have access to substrates that cannot be reached under normal conditions.…”
Section: Discussionsupporting
confidence: 87%
“…This disparity is due to rapid degradation by the ubiquitin/proteasomal system (22). We used a transgenic mouse strain with insertion of a bacterial artificial chromosome (BAC) containing the whole-mouse SGK1 gene (Ϸ200 kb) modified by the addition of three HA epitopes at the C terminus of the coding region (23). In tissue homogenates of brain, heart, and lung, we identified SGK1 (49/45 kDa) and SGK1.1 (60 kDa) only in brain ( Fig.…”
Section: Sgk1 Splice Isoforms and Distribution In Mousementioning
confidence: 99%
“…In particular, it is interesting to recall recent studies that showed the existence of 4 independent SGK1 products that arise because of use of alternate start sites during translation (32). Interestingly, we observed that although 4 separate SGK1 variants are consistently expressed in total cellular lysates (Fig.…”
Section: Gilz1 and Sgk1 Synergistically Stimulate Enac Cell Surface Ementioning
confidence: 50%
“…The effect of GILZ1 seems to be selectively on the longer SGK1 product that presumably has the N terminus intact. In this context, it is pertinent to recall earlier studies from our laboratory and others that showed that the N terminus of SGK1 is important for its ENaC-stimulatory activities via Nedd4-2 inhibition (5,32). Further studies will be needed to elucidate the role of the N terminus and PY motif of SGK1 in the context of the ENaC regulatory complex.…”
Section: Gilz1 and Sgk1 Synergistically Stimulate Enac Cell Surface Ementioning
confidence: 97%
“…It was proposed that leaky scanning is the mechanism responsible for the synthesis of these protein variants characterized by different stabilities, subcellular localizations and functions. (36) Similarly, alternative TIS and leaky scanning are used to produce functionally different isoforms of a regulator of G-protein signaling (RGS2) and human glucocorticoid receptor (hGRalpha). (37,38) IRES can also mediate the translation of several protein isoforms with different subcellular localizations: for example, fibroblast growth factor-2 (FGF-2) can be produced as distinct isoforms by the alternative initiation of translation on an IRES-containing mRNA and these isoforms are differently sorted in cells.…”
Section: Types Of Alternative Open Reading Framesmentioning
confidence: 99%